Differentiation of Plio-Pleistocene Hominids. I. Morphological and ecological Characteristics - Kaszycka, Katarzyna (Anthropological Review, 1984)
The work presents contemporary views concerning the morphological and ecological characteristics of the oldest representatives of Hominidae family, the Plio-Pleistocene australopithecine, their dating, taxonomy, and origin. The morphology of these early hominids is characterized by the locomotor system, the masticatory apparatus, body size and brain size. Whereas the traits of the łocomotor system of australopithecines indicate that the forms (species) of Plio-Pleistocene hominids were completely bipedal, and the majority of morphological traits of their lower limbs were within the variability of Homo sapiens (tables 2 and 3), the remaining traits differ the particular species among each other. In the traits of the masticatory apparatus, aside of the characteristic postcanine megadontia, noteworthy is the different proportion of the anterior teeth size to the posterior teeth size in the gracile and robust forms. The evaluation of the body height and weight, except for quantitative differences, suggest a distinctly greater sexual dimorphism among robust individuals, than among the gracile ones. On the other hand, the character of the proportion of the cranial capacity and the body weight for Hominidae family (fig. 7) determined by Henneberg [1984] places the Australopithecus robustus beyond the line of our immediate ancestors. Numerous morphological traits, excavation sites, and purposefully shaped tools accompanying the skeletal remains supply premises for ecological considerations. Thus, it is likely that australopithecine populations lived in fairly large groups and already had some primitive social organization characteristic of the primitive hunter-gatherers.